Impact of personalized nursing on the quality of life in lung cancer patients - Liu, Ying; Guo, Huan (Frontiers in Oncology, 2025)
BackgroundLung cancer remains a leading cause of cancer-related morbidity and mortality worldwide. As systemic therapy prolongs survival, improving patients’ quality of life (QoL) has become a central goal of holistic care. Personalized nursing interventions, tailored to individual patient needs, have shown promise in oncology but lack large-scale evaluation in lung cancer populations.MethodsThis retrospective cohort study analyzed 291 patients diagnosed with stage II–IV lung cancer who underwent systemic treatment at Hubei Cancer Hospital, Tongji Medical College, Huazhong University of Science and Technology between January 2022 and December 2024. Patients were categorized into two groups: the intervention group (n = 137), who received personalized nursing care based on individualized symptom assessment, psychological support, and lifestyle counseling; and the control group (n = 154), who received standard nursing care. QoL was assessed using the EORTC QLQ-C30 questionnaire at baseline and at 8 weeks post-intervention. Secondary outcomes included emotional distress (measured by HADS), treatment adherence, and unplanned healthcare utilization.ResultsThe personalized nursing group demonstrated a significantly greater improvement in overall QoL scores at 8 weeks (mean change: +13.2 ± 7.6 vs. +5.1 ± 6.8, P < 0.001). Notable improvements were also observed in emotional functioning, fatigue, and pain subscales (all P < 0.01). Anxiety and depression scores were significantly reduced in the intervention group (mean HADS total: 12.5 ± 4.1 vs. 16.8 ± 5.3, P < 0.001). Treatment adherence was higher (91.2% vs. 78.6%, P = 0.006), and fewer unplanned clinic visits or emergency admissions were reported (12.4% vs. 23.4%, P = 0.014).ConclusionPersonalized nursing interventions significantly enhance quality of life, emotional well-being, and care adherence in patients with lung cancer. These findings support the integration of individualized nursing strategies into routine oncology practice to optimize both physical and psychological outcomes in this population.